The Effect of Combined Cold Air and Minimum Liquid Cooling on End Milling - Boswell, Brian; Voges, E. (Information Engineering Research Institute, 2011)
Modern machining companies constantly face the challenges of quality and cost pressures as well as the ever increasing global awareness of social and environmental issues that affect the manufacturing of machined parts. For companies to remain competitive and sustainable in the future they need to develop new techniques which reduce the environmental impact of manufacturing. Conventional wisdom [1] states that it is essential to use flood coolant to reduce thermal shock on the tool tip during end milling, as intermittent cooling increases this effect. End milling dry is preferred to milling with too little cutting fluid for this reason, especially for carbide tool tips. Previous experimental evaluation of Minimal Quantities of Lubrication (MQL) when applied to an end milling operation has proved to be inconclusive as to the effectiveness. The cause is believed to be ineffective heat removal from the cutting zone. The research presented in this paper represents the initial experimentation involved in developing a suitable alternative approach to using copious amounts of cutting fluid during end milling. It has been found from cutting tests that eliminating the cutting fluid entirely has not been practical: the most promising results have been derived from a combination of air cooling with the addition of small amounts of vegetable oil.